Post-discharge oral antimicrobial use among hospitalized patients across an integrated national healthcare network. (March 2020) - Feller, J.; Lund, B.C.; Perencevich, E.N.; Alexander, B.; Heintz, B.; Beck, B.; Nair, R.; Goto, M.; Livorsi, D.J.
Abstract: Objectives: Antimicrobial stewardship programmes have focused on reducing inappropriate inpatient antimicrobial prescribing, but several small studies have found a large portion of antimicrobial exposure occurs immediately after hospital discharge. In this study, we describe the prescribing of oral antimicrobials at hospital discharge across an integrated national healthcare system. At the hospital level, we also compare total inpatient antimicrobial use and post-discharge oral antimicrobial use. Methods: This retrospective cross-sectional study used national administrative data to identify all acute-care admissions during 2014–2016 within the Veterans Health Administration (VHA). We evaluated inpatient days of therapy (DOT) and post-discharge DOT, defined as oral outpatient antimicrobials dispensed at the time of hospital discharge. At the hospital level, inpatient DOT/100 admissions were compared with post-discharge DOT/100 admissions using Spearman's rank-order correlation. Results: There were 1 681 701 acute-care admissions across 122 hospitals, and 335 369 (19.9%) were prescribed an oral antimicrobial at discharge. Fluoroquinolones (38.3%) were the most common post-discharge antimicrobial. At the hospital level, median inpatient antimicrobial use was 331.3 (interquartile range (IQR) 284.9–367.9) DOT/100 admissions and median post-discharge use was 209.5 (IQR 181.5–239.6) DOT/100 admissions. Thirty-nine per cent of the total duration of antimicrobial exposure occurred after discharge. At the hospital-level, the metrics of inpatient DOT/100 admissions and post-discharge DOT/100 admissions were weakly positively correlated with rho=0.44 (p < 0.001). Conclusions: A large proportion of antimicrobial exposure among hospitalized patients occurred immediately following discharge. Antimicrobial-prescribing at hospital discharge provides an opportunity for antimicrobial stewardship. Hospital-level stewardship metrics need to include both inpatient and post-discharge antimicrobial-prescribing to provide a comprehensive assessment of hospital-associated antimicrobial use.